Double C-H functionalization Iodo-compound mediated cyclization of aryl aldehyde - Chan, Min Kang (2015)
Carbon–Hydrogen bond (C–H) activation offers chemists a direct route to perform chemical transformation on simple and complex molecules without prior functionalization on the structure. It also allows previously hard to access chemical feedstock to be directly manipulated to more useful chemical intermediates. New advances in organometallic chemistry and novel catalysts have kindled a fast growing interest in this research area where it was previously thought to be inaccessible. The author reported on the development of a novel double C–H activation between aldehyde C–H and arene C–H, based on the lessons learned in the author’s group research in to Rhodium-catalyzed coupling reactions and other Palladium-catalyzed coupling reaction. The C–H activation was found to proceed with or without rhodium catalyst in the presence of iodo-based oxidants or molecular iodine. The intramolecular reaction provides a facile method for the synthesis of aryl ketones and aromatic systems